PENGARUH MOTIVASI KERJA, KOMPETENSI MENGAJAR DAN KEPRIBADIAN GURU TERHADAP KINERJA GURU DI SMS 46 JAKARTA - Siregar, Edi; Efi Nefiyanti (Pasca Sarjana Universitas Satya Negara Indonesia, 2017)
“The effect of Work Motivation, Teaching Competence and Personality of the Teacher on Teacher Performance in Senior High School 46 Jakarta”. Program Pascasarjana Universitas Satya Negara Indonesia..The results showed that either partially or jointly variable Work Motivation, Teaching Competency and Teacher Personality significant effect on performance, with details as follows: 1).Work motivation significant effect on the Performance of teachers, it can be proved with sig = 0.018 <0.05, and t count 2,425> 1,999 t table; 2. Teacher Competence significant effect on the performance of teachers, it can be proved with sig = 0.023 <0.05, and t count 2,334> t table 1,999; 3. Personality of teacher significant effect on the performance of teachers, it can be proved with sig = 0.013 <0.05, and 2.566 t count> t table 1,999; 4. Work motivation, competence and personality of the teacher together a significant effect on the performance of teachers, it can be proved with sig = 0.000 <0.05, and 19.511 F count> F table 2.758.